KHILAFAHISASI HIZBUT TAHRIR INDONESIA (HTI) MELALUI DUNIA DIGITAL DI INDONESIA - Syarafuddin H Zainuddin; Zaki Faddad SZ (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2017)
The idea of ummah in the notion of khilafah (one rule of the world) is probably not realistic enough for most Muslims in Indonesia. Even call it a utopian dream. However, the concept of nationalism in a nation state has become an established reality. Therefore, this article will examine how HTI spread its ideas and the opportunities it gets. This research uses framing process analysis in the study of social movement. From that approach it can be concluded that HTI in its propaganda always highlight the issues of Indonesianness for the ultimate goal of introducing the khilafah. After that HTI tries to provide understanding and optimism about its utopian idealism, and changes the imaginary ideas about the khilafah as if factual to solve the problems of Indonesia